Axial Length in Retinal Vein Occlusion - MirNaghi Mousavi; Mohammad Hashem Naseri; Naser Shoeibi (Patient Safety and Quality Improvement Journal, 2015)
Introduction: Retinal vein occlusion is one of the most common forms of vascular disease in retina, and leads to visual loss in patients. Various treatment options were proposed for this disorder. The aim of this study was to compare axial length in eye with retinal vein occlusion in comparison with intact eye. Materials and Methods: After ethical approval, this case-control study was designed in Mashhad University of medical sciences. We selected 63 patients with retinal vein occlusion and 23 control group. Axial length was measured by a mode scan (NIDEK-US 4000, Japan), macular thickness (macular edema) was evaluated by Optical Coherence Tomography (ZEISS, Germany). Data were analyzed with SPSS Version 16. P